Review Literature: Relationship of Food Intake and the Incidence of Dyspepsia Syndrome in Medical Students - Napitupulu, Cindy Cecilia Anasthasya; Rahmanisa, Soraya; Happy, Terza Aflika; Sari, Ratna Dewi Puspita (Medula, 2025)
Dyspepsia syndrome is a digestive disorder characterized by symptoms such as epigastric pain, burning, bloating and nausea. In Indonesia, the prevalence is high, with most cases classified as functional dyspepsia. In medical students, poor and irregular diets are common due to academic pressure, busy schedules, and unhealthy lifestyles, which are thought to be the main risk factors for dyspepsia. These habits are further exacerbated by the consumption of unhealthy foods, such as fast food, as well as the habit of eating at irregular times. This study aimed to evaluate the relationship between diet and the incidence of dyspepsia syndrome in medical students in Indonesia through a literature review. A literature search was conducted online using Google Scholar with the keywords “dyspepsia syndrome,” “medical student dyspepsia syndrome,” and “medical student diet.” Of the 635 articles found, 16 were screened based on relevance of content, availability of full text, use of Indonesian language, and time of publication within the last 5 years. Five relevant articles were selected for further review. The review showed a significant association between disordered eating patterns and the incidence of dyspeptic syndrome. Habitual skipping of breakfast, consumption of fast food, eating under stressful conditions, and lack of balanced nutritional intake contributed to the risk of dyspepsia. This conclusion emphasizes the importance of health education on regular diet, stress management, and healthy lifestyle to prevent dyspepsia syndrome and improve the quality of life of medical students.